2017
DOI: 10.1016/j.cpr.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault victimization and psychopathology: A review and meta-analysis

Abstract: Sexual assault (SA) is a common and deleterious form of trauma. Over 40 years of research on its impact has suggested that SA has particularly severe effects on a variety of forms of psychopathology, and has highlighted unique aspects of SA as a form of trauma that contribute to these outcomes. The goal of this meta-analytic review was to synthesize the empirical literature from 1970–2014 (reflecting 497 effect sizes) to understand the degree to which (a) SA confers general risk for psychological dysfunction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
441
1
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 580 publications
(512 citation statements)
references
References 91 publications
16
441
1
13
Order By: Relevance
“…Thus, a recent meta-analysis has shown that sexual abuse experience more than other trauma types has clear ties to a higher incidence of mood, anxiety or substance use disorders, even independently from PTSD (Dworkin et al, 2017). Interestingly, these conditions were also found to be more likely among individuals with chronic PTSD than among those with faster symptom improvement (Chapman et al, 2012;McFarlane, 2000;Zlotnick et al, 2004;Zlotnick et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a recent meta-analysis has shown that sexual abuse experience more than other trauma types has clear ties to a higher incidence of mood, anxiety or substance use disorders, even independently from PTSD (Dworkin et al, 2017). Interestingly, these conditions were also found to be more likely among individuals with chronic PTSD than among those with faster symptom improvement (Chapman et al, 2012;McFarlane, 2000;Zlotnick et al, 2004;Zlotnick et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a representative sample, Forbes and colleagues (2014) found that violence by an intimate perpetrator (including caregivers and romantic partners) was linked to greater PTSD symptom severity relative to both interpersonal traumatic events by non-intimates and to non-interpersonal event exposure. However, a recent meta-analysis of the psychological impact of SA suggested that stranger-perpetrated SA may be associated with greater symptom severity than SA perpetrated by a known assailant (Dworkin et al, 2016). Experiencing traumas committed by different perpetrators (as in SA revictimization) is associated with the passive avoidance and arousal symptoms of PTSD (Matlow & DePrince, 2012).…”
mentioning
confidence: 99%
“…Almost 25% of individuals who died as young adults (vs 10% in class 2) were victims of intrafamily sexual violence between ages 10 and 14. The literature presents robust evidence that childhood sexual assault pervasively undermines the mental health equilibrium 45 and leads to higher risk of suicidal outcomes 32,33 . Much scarcer is the evidence about the consequences of intrafamily sexual violence occurring during adolescence.…”
Section: Discussionmentioning
confidence: 99%